Are consumer expectations theory-consistent? The role of macroeconomic determinants and central bank communication - Lena Dräger; Michael J. Lamla; Damjan Pfajfar (ETH Zurich, KOF Swiss Economic Institute, 2013)
Using the microdata of the Michigan Survey of Consumers, we evaluate whether U.S. consumers form macroeconomic expectations consistent with different economic concepts. We check whether their expectations are in line with the Phillips Curve, the Taylor Rule and the Income Fisher Equation. We observe that 50% of the surveyed population have expectations consistent with the Income Fisher equation and the Taylor Rule, while 25% are in line with the Phillips Curve. However, only 6% of consumers form theory-consistent expectations with respect to all three concepts. For the Taylor Rule and the Phillips curve we observe a strong cyclical pattern. For all three concepts we find significant differences across demographic groups. Evaluating determinants of consistency, we provide evidence that the likelihood of having theory-consistent expectations with respect to the Phillips curve and the Taylor rule falls during recessions and with inflation higher than 2%. Moreover, consistency with respect to all three concepts is affected by changes in the communication policy of the Fed, where the strongest positive effect on consistency comes from the introduction of the official inflation target. Finally, we show that consumers with theory-consistent expectations have lower absolute inflation forecast errors and are closer to professionals' inflation forecasts.
Keywords: C25; D84; E31; 330; macroeconomic expectations; microdata; macroeconomic literacy; central bank communication; consumer forecast accuracy